Methodological bases for the introduction of health-preserving technologies into the young people’s physical education system - Hovhannisyan, Sahak (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
In the modern physical education system, the process of forming a health-preserving educational environment, particularly introducing health-preserving technologies, the successful implementation of which involves a complex solution of a number of research tasks, is of specific importance. The urgency of examining the possibilities of using health-preserving technologies in higher educational establishments is caused by the average level of the current students’ academic performance, conditioned by the high degree of their illness incidence. Besides, the health of students is considered as an indicator of the quality of their proficiency, social and creative activeness, as an economic outcome that ensures the competitiveness of a future specialist in the labor market. In this context, the need of formation of a higher valeological culture among the contemporary students, as well as development of a comprehensive methodology for introducing health-preserving technologies into the physical education system of universities, are specially emphasized. This article refers to the operating mechanisms and current approaches for perception of health-preserving technologies and their implementation. Accordingly, the health-saving technologies introduced in this study are presented as a complex innovative process, which should be based on a systematic and harmonious interaction of all participants in the pedagogical process with the educational environment, as well as value changes in their attitude to health and educational activities. Therefore, when introducing health-saving technologies into the system of physical education of students, it is also necessary to take into account their gender and age characteristics and functional capabilities.
Keywords: physical education; education; health-improving function; integrated approach; healthy lifestyle; functional state; health-preserving technologies